2018
DOI: 10.1016/j.compstruc.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Axisymmetric semi-analytical finite elements for modelling waves in buried/submerged fluid-filled waveguides

Abstract: Efficient and accurate predictions of wave propagation are a vital component of wave-based nondestructive interrogation techniques. Although a variety of models are available in the literature, most of them are suited to a particular wave type or a specific frequency regime. In this paper we present a multi-wave model for wave propagation in axisymmetric fluid-filled waveguides, either buried or submerged in a fluid, based on the semi-analytical finite elements. The cross-section is discretised with high-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…This illustrates the complexity of this type of coupled guided wave problem and this is behaviour that has been shown before [13]. Of course, it is also well known that the compressional modes never cross one another in the dispersion curves of a lossless system, and instead they avoid crossing, or veer apart, as the energy is transferred between the fluid and the structure [12,21].…”
Section: Tablesupporting
confidence: 54%
See 2 more Smart Citations
“…This illustrates the complexity of this type of coupled guided wave problem and this is behaviour that has been shown before [13]. Of course, it is also well known that the compressional modes never cross one another in the dispersion curves of a lossless system, and instead they avoid crossing, or veer apart, as the energy is transferred between the fluid and the structure [12,21].…”
Section: Tablesupporting
confidence: 54%
“…Both analytic and numerical methods have been developed, see for example the commercial code DISPERSE®, which uses an analytic solution for the coupled problem [19]. More recently, alternative numerical approaches have been developed, including the wave finite element method [20], and the semi analytic finite element (SAFE) method [21]. These numerical models have been applied to liquid filled pipes and demonstrate that large numbers of eigenmodes can readily be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, finite-element methods are commonly used to model the wave propagation in buried pipe systems. Relevant research can be found in [79]. Recent studies have shown that the fluid-dominated wave can radiate effectively into surrounding soil, based on which the location of buried pipes can be inferred through monitoring the ground surface vibration using for example geophones [69].…”
Section: Appl Sci 2020 10 X For Peer Review 3 Of 34mentioning
confidence: 99%
“…Alternatively, finite-element methods are commonly used to model the wave propagation in buried pipe systems. Relevant research can be found in [79].…”
Section: Appl Sci 2020 10 X For Peer Review 3 Of 34mentioning
confidence: 99%